Relevansi Ta’aruf sebagai Alternatif Menghindari Pacaran dalam Islam (International Forum of Researchers and Lecturers, 2023)
Ta’aruf is a process of introduction between two individuals aimed at building a more serious relationship within the context of marriage. In modern society, dating is often considered a preliminary step toward marriage; however, from an Islamic perspective, dating can lead to various moral and social problems. This journal aims to explore the relevance of ta’aruf as a more appropriate alternative aligned with Islamic values in avoiding dating. Through theoretical reviews, research methodology, and data analysis, this study seeks to provide effective solutions to the challenges of relationships among Muslim youth. The findings indicate that ta’aruf has a strong foundation in Islamic teachings and offers a safe space for individuals to get to know each other in a shar’i (lawful) manner without violating religious boundaries. This process not only minimizes the potential for moral pitfalls but also fosters a healthier and more purposeful foundation of communication toward a harmonious marriage (sakinah). With the right approach, ta’aruf can serve as a relevant, adaptive model of pre-marital relationships that educates young Muslims to build families based on Islamic values.